2016
DOI: 10.1016/j.neurobiolaging.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Insensitivity of astrocytes to interleukin 10 signaling following peripheral immune challenge results in prolonged microglial activation in the aged brain

Abstract: Immune-activated microglia from aged mice produce exaggerated levels of cytokines. Despite high levels of microglial IL-10 in the aged brain, neuroinflammation was prolonged and associated with depressive-like deficits. Because astrocytes respond to IL-10 and, in turn, attenuate microglial activation, we investigated if astrocyte-mediated resolution of microglial activation was impaired with age. Here, aged astrocytes had a dysfunctional profile with higher GFAP, lower glutamate transporter expression, and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 85 publications
2
44
0
Order By: Relevance
“…It is likely that while peak cytokine responses during intoxication could remain stable across age, the resolution of the inflammatory response could differ across ontogeny. Prior work has shown that the aged neuroimmune system can exhibit protracted neuroimmune activation following a peripheral immune challenge (Norden et al, 2016; Huang, Henry, Dantzer, Johnson, & Godbout, 2008). While a rapid resolution of RANGE is seen at 18 h in adult rats, examination of this time point in aged animals may yield alternative results that would help inform conclusions regarding alcohol effects on neuroimmune function in late aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that while peak cytokine responses during intoxication could remain stable across age, the resolution of the inflammatory response could differ across ontogeny. Prior work has shown that the aged neuroimmune system can exhibit protracted neuroimmune activation following a peripheral immune challenge (Norden et al, 2016; Huang, Henry, Dantzer, Johnson, & Godbout, 2008). While a rapid resolution of RANGE is seen at 18 h in adult rats, examination of this time point in aged animals may yield alternative results that would help inform conclusions regarding alcohol effects on neuroimmune function in late aging.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, blunted peripheral expression of anti-inflammatory cytokines such as IL-10 has been shown in the aged animal following immune challenge and spinal cord injury models as compared to young controls (Williams, José, Brown, & Chambers, 2015; Zhang, Bailey, Braun, & Gensel, 2015). In the brain, exaggerated levels of cytokines are associated with aging, yet insensitivity to the effects of anti-inflammatory cytokines such as IL-10 has been reported, indicating shifts in the regulation of neuroinflammation (Norden, Trojanowski, Walker, & Godbout, 2016). Consistent with this, aged mice have been shown to exhibit sensitized cytokine responses and a protracted recovery from immune challenge (Huang, Henry, Dantzer, Johnson, & Godbout, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, if we consider findings from aged rodents, this is not a surprising notion. Aged rodents are far more vulnerable to the consequences of immune activation compared with younger animals (Bilbo, ; Liu et al, ; Norden et al, ; for a review see Niraula et al, ) and, in humans cognitive impairments observed in the aged population following infection or illness are prolonged and more severe relative to a younger population (Bodles and Barger, ; Perry, ). Much like aging, it is likely that earlier periods of neural development (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Under homeostatic conditions, astrocytes respond to microgliainduced inflammatory stimulation by producing antiinflammatory cytokines such as IL-10 and TGF-β, which act as a feedback loop to decrease microglial activation (Norden et al, 2015b(Norden et al, , 2016. Aged astrocytes fail to restrain microglial activation probably due to a loss of or decreased surface expression IL-10 receptors in older compared with younger astrocytes (Norden et al, 2015b(Norden et al, , 2016.…”
Section: Alternative Activation and Acquired Deactivation Statesmentioning
confidence: 99%